2021
DOI: 10.7150/ijbs.60401
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Suppresses the Proliferation, Migration and Invasiveness through Regulating ROS, Autophagic Flux and miR-877-5p in Human Bladder Carcinoma Cells

Abstract: Bladder carcinoma is among the top 10 most frequently diagnosed cancer types in the world. As a phytochemical active metabolic, thymoquinone (TQ) is extracted from seeds of Nigella sativa, possessing various biological properties in a wide range of diseases. Moreover, the outstanding anti-cancer effect of TQ is attracting increasing attentions. In certain circumstances, moderate autophagy is regarded to facilitate the adaptation of malignant cells to different stressors. Conversely, closely linked with the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Moderate autophagy has the positive effect to resist stress damage and inhibit cellular apoptosis. 15 Trehalose protected many pathological conditions-induced apoptosis by promoting autophagy. 16,17 All this evident indicated that Trehalose might prevent the lipotoxicity-induced apoptosis of osteoblasts by enhancing autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate autophagy has the positive effect to resist stress damage and inhibit cellular apoptosis. 15 Trehalose protected many pathological conditions-induced apoptosis by promoting autophagy. 16,17 All this evident indicated that Trehalose might prevent the lipotoxicity-induced apoptosis of osteoblasts by enhancing autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are small noncoding RNAs that modulate gene expression and cellular signaling pathways through variation in the features of mRNA, thus moderating TQ’s anticancer effect through P53, PCNA, cyclin D1, Bcl-2, NF-κB, TWIST (Twist1,2), ZEB, eEF-2 K, PI3K/Akt, and Src/Fak signaling pathways [ 247 ]. Along with TQ’s impairment of autophagic flux and inhibition of the EMT and cell invasion via activation of the miR-877-5p/PD-L1 (programmed death ligand 1) axis in bladder carcinoma cells and the expression of Beclin-1 and LC3 in triple-negative breast cancer (TNBC) cells, it suppresses the pathways related to cell migration/invasion and angiogenesis, including Integrin-β1, VEGF, MMP-2, and MMP-9 [ 248 , 249 ]. Thymoquinone upregulates miR-125a-5p, attenuates STAT3 activation, and potentiates doxorubicin antitumor activity in murine solid Ehrlich carcinoma [ 250 ].…”
Section: Plant-derived Natural Products With Potential Anticancer Eff...mentioning
confidence: 99%
“…hsa-miR-877-5p levels were found to be enhanced in tumor xenografts in mice inoculated with T24 cells. Moreover, thymoquinone profoundly suppressed the number of pulmonary metastatic nodules in mice injected with bladder cancer cells [ 99 ].…”
Section: Regulation Of Micrornas By Thymoquinonementioning
confidence: 99%